1995
DOI: 10.1038/nm1095-1046
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of betulinic acid as a selective inhibitor of human melanoma that functions by induction of apoptosis

Abstract: As a result of bioassay-guided fractionation, betulinic acid, a pentacyclic triterpene, was identified as a melanoma-specific cytotoxic agent. In follow-up studies conducted with athymic mice carrying human melanomas, tumour growth was completely inhibited without toxicity. As judged by a variety of cellular responses, antitumour activity was mediated by the induction of apoptosis. Betulinic acid is inexpensive and available in abundant supply from common natural sources, notably the bark of white birch trees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
539
0
10

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 770 publications
(572 citation statements)
references
References 21 publications
13
539
0
10
Order By: Relevance
“…Other pentacyclic triterpenes such as oleanane and ursane could not differentiate B16 2F2 cells. Previously, it was reported that compound 10 was a selective anticancer agent against some human cancer cell lines (Fulda et al 1999;Pisha et al 1995;Schmidt et al 1997), and the carboxyl group at the C-17 was essential for apoptotic activities (Lee et al 1998). In our studies of anti-proliferative effects by these triterpenes on B16 2F2 cells, compounds 8-12, all of which have a carbonyl group at C-17, were found to inhibit B16 2F2 cell proliferation at lower concentrations than other compounds.…”
Section: Structure-activity Relationships Of Melanogenesis and Apoptomentioning
confidence: 62%
“…Other pentacyclic triterpenes such as oleanane and ursane could not differentiate B16 2F2 cells. Previously, it was reported that compound 10 was a selective anticancer agent against some human cancer cell lines (Fulda et al 1999;Pisha et al 1995;Schmidt et al 1997), and the carboxyl group at the C-17 was essential for apoptotic activities (Lee et al 1998). In our studies of anti-proliferative effects by these triterpenes on B16 2F2 cells, compounds 8-12, all of which have a carbonyl group at C-17, were found to inhibit B16 2F2 cell proliferation at lower concentrations than other compounds.…”
Section: Structure-activity Relationships Of Melanogenesis and Apoptomentioning
confidence: 62%
“…20 The activity found with 16 against intracellular Leishmania, without substantial toxicity for host cells, points to the interest of carrying out further tests of this compound on animal models. The mechanism of action of betulin and betulin derivatives has been only partially explored (it prevents DNA cleavage and the formation of topoisomerase-DNA complex), 18,[27][28][29] and internalization by Leishmania is unknown. It is interesting to note that the most active derivative exhibited a higher inhibitory activity against amastigotes than against promastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…with saline (0.1 ml), BA (10 mg kg À1 day À1 ), VCR (0.065 mg kg À1 day À1 ) or a combination of both drugs (BA, 10 mg kg À1 day À1 ; VCR, 0.065 mg kg À1 day À1 ) (Figure 1). The dose of BA for the treatment of mice was decided by referring to a previous report (Pisha et al, 1995). Body weights of mice were recorded every 4 days to determine whether the treatment influenced health status.…”
Section: Drug Interaction Analysismentioning
confidence: 99%
“…Betulinic acid (BA), a pentacyclic triterpene isolated from the root bark of Morus australis or Clerodendrum mandarinorum and many other medicinal plants (Zhu et al, 1996;Ko et al, 1997), has recently been reported to have cytotoxic activity against several tumour cell lines (Pisha et al, 1995;Fulda et al, 1997Fulda et al, , 1998Wick et al, 1999;Kwon et al, 2002;Wachsberger et al, 2002). Betulinic acid is a novel experimental antineoplastic agent for human melanoma cells in vitro (Pisha et al, 1995;Wachsberger et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation